Kombinasi Lesi Badan Negri, Spongiform, dan Perivascular Cuffing pada Otak Anjing Penderita Rabies (THE COMBINATION OF NEGRI BODIES, SPONGIFORM, AND PERIVASCULAR CUFFING IN RABIES AFFECTED DOG’S BRAIN) - Berata, I Ketut; Kardena, I Made; Winaya, Ida Bagus Oka; Supartika, I Ketut Eli (Jurnal Veteriner, 2014)
A relatively high incidence of spongiform lesions (61%) and perivascular cuffing (89%) in brains ofdogs that suffered from rabies in Bali was an interesting background to do further studied. This study aimwas to identify the association between Negri bodies, spongiform and perivascular cuffing in dog’s brainthat infected with rabies in Bali. The research used 28 of dog’s brain samples infected with rabies and havebeen diagnosed using fluorescence antibody technique (FAT) in the Veterinary Disease InvestigationCenter, of Denpasar. Each of the brain samples contained of cerebrum, cerebellum and hippocampus thatwere taken for histological examination using hematoxylin-eosin staining. The presence of negri bodies,spongiform, and perivascular cuffing were analyzed for their association. The results showed thatcombination lesions of Negri bodies and spongiform found in the cerebellum (14%), cerebrum (4%), andhippocampus (32%), while combination lesions of perivascular cuffing and Negri bodies found in cerebellum(18%), cerebrum (7%), and hippocampus (43%). The highest intensity combination lesion of Negri bodiesand spongiform was found in hippocampus compared to the cerebellum and cerebrum. The highest intensityfor combination of spongiform and perivascular cuffing was found in cerebrum 50%, cerebellum 32%, andhippocampus 36%. It can be concluded that there might be association between the existence of Negribodies and perivascular cuffing lesions with the existed area of rabies infected dog’s brain, but not likely asspongiform.
Keywords: negri bodies, spongiform, perivascular cuffing